Theodor Adorno and the century of negative identity - Oberle, Eric, 1986- (Cultural memory in the present., 2018)
Covering the period of the Frankfurt School's exile in the United States, this book examines how the critique of racism, authoritarianism, and hard-right agitation impacted the American and German individual's self-conception (identity), while examining how a new form of politics, based on defining an Other, has shaped our everyday language, institutions, and social world.